The National Early Childhood Care and Education Curriculum Framework, 2014, and its Implications for Practice - Pandya, Kinnari (Voices of Teachers and Teacher Educators, 2018)
National Early Childhood Care and Education Curriculum Framework 2014 is a significant milestone in articulating the key objectives of an early childhood program and process important for an early childhood teacher and a centre to follow. This paper examines the ECCE curriculum framework on parameters outlined for a Curriculum Framework in the position paper of the National Focus Group on Curriculum, Syllabus and Textbooks brought out by the NCERT. Alongside, it provides an overview of the National ECCE curriculum framework. Further, it suggests some necessary steps required to translate the aims articulated in the curriculum framework to prepare and educate all stakeholders involved in offering early childhood programs – parents, teacher educators, teachers, caregivers, centre managers, other functionaries engaged with planning and implementing early childhood programs.